2008
DOI: 10.1667/rr1150.1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Alveolar Macrophages after Plutonium Oxide Inhalation in Rats: Involvement in the Early Inflammatory Response

Abstract: Alveolar macrophages play an important role in the distribution, clearance and inflammatory reactions after particle inhalation, which may influence long-term events such as fibrosis and tumorigenesis. The objectives of the present study were to investigate the early inflammatory events after plutonium oxide inhalation in rats and involvement of alveolar macrophages. Lung changes were studied from 3 days to 3 months after inhalation of PuO2 of different isotopic compositions (70% or 97% 239Pu) and initial lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Similarly to what we described after Pu contamination (Van der Meeren et al 2008, CD68 positive cells were increased after MOX. Because CD68 is expressed on all macrophages (Murray and Wynn 2011), we used specifi c markers for M1 and M2 phenotypes.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to what we described after Pu contamination (Van der Meeren et al 2008, CD68 positive cells were increased after MOX. Because CD68 is expressed on all macrophages (Murray and Wynn 2011), we used specifi c markers for M1 and M2 phenotypes.…”
Section: Discussionsupporting
confidence: 86%
“…There is the suggestion therefore that radiation-induced enhancement of inflammatory reactions might contribute to the development of radiation-induced disorders and premature ageing [155,161]. Indeed, it is also well known that A-bomb survivors show increased cardiovascular and respiratory diseases associated with persistent inflammation [162,163]. …”
Section: Ionising Radiation and Senescencementioning
confidence: 99%
“…Irradiated macrophages through release of "biochemical cues" may result in cellular transformation and ultimately carcinogenesis. Evidence for macrophage activation both immunohistochemical and cytokine production at early times (14 d) after plutonium oxide inhalation (5-10 kBq) has been recently demonstrated (Van der Meeren et al 2008). However, inflammatory responses may not always be concomitant with epithelial proliferation, as Taya et al (1993) showed in mice proliferation of epithelial cells at least 1 mo after exposure.…”
Section: Localization Of Lung Radioactivitymentioning
confidence: 99%